2019
DOI: 10.1007/s12325-019-00923-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival, Motor Function, and Motor Milestones: Comparison of AVXS-101 Relative to Nusinersen for the Treatment of Infants with Spinal Muscular Atrophy Type 1

Abstract: IntroductionInfants with spinal muscular atrophy (SMA) type 1 typically face a decline in motor function and a severely shortened life expectancy. Clinical trials for SMA type 1 therapies, onasemnogene abeparvovec (AVXS-101) and nusinersen, demonstrated meaningful improvements in efficacy (e.g., overall survival) but there were no head-to-head clinical trials assessing comparative efficacy. This study estimated the treatment effects of AVXS-101 relative to nusinersen for the treatment of SMA type 1.MethodsOver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(49 citation statements)
references
References 25 publications
(44 reference statements)
0
46
0
1
Order By: Relevance
“…Authors demonstrated an efficacy advantage of onasemnogene abeparvosec in terms of motor milestones achieved, motor function (CHOP-INTEND score) improvement and independence from permanent assisted ventilation. Moreover, the probability of preventing death was 20% higher in the onasemnogene abeparvosec treated group [ 90 ]. However, the main drawback of this study is the use of an unanchored indirect analysis of NNT between two studies.…”
Section: Discussionmentioning
confidence: 99%
“…Authors demonstrated an efficacy advantage of onasemnogene abeparvosec in terms of motor milestones achieved, motor function (CHOP-INTEND score) improvement and independence from permanent assisted ventilation. Moreover, the probability of preventing death was 20% higher in the onasemnogene abeparvosec treated group [ 90 ]. However, the main drawback of this study is the use of an unanchored indirect analysis of NNT between two studies.…”
Section: Discussionmentioning
confidence: 99%
“…13 The vector crosses the blood-brain barrier and transports the gene to the motor neuron cells in the central nervous system. 13,14 After administration, the shed vector DNA was found in the saliva, urine, and stool. 11 Concentrations were undetectable at 3 weeks in the saliva and urine and by 1 to 2 months in the stool.…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…Despite there having been no study directly comparing Zolgensma to Spinraza to date, several papers have provided indirect comparisons. In general, these report a no difference in clinical efficacy, or a slight benefit leaning towards the use of Zolgensma [90]. Similarly, in terms of cost-effectiveness, the two therapies would appear to be similar, with Zolgensma again potentially being slightly cheaper long-term [91].…”
Section: The Discovery Of the First Sma Drugmentioning
confidence: 93%